The defensor civitatis for the Protection of Vulnerable People - M. Lourdes Martinez de Morentin (Journal of Interdisciplinary History of Ideas)
This article considers the Roman defensor civitatis, which has been seen as an ancient precedent for the ombudsman for the people. Similar to the current ombudsman, he protected the most vulnerable people. This figure, since the beginning of the Ombudsman in the Swedish Constitution of 1809, has spread in States with a social and democratic conscience and is present in all areas of social life. Its creation has been one of the great advances of the Rule of Law from the point of view of guaranteeing fundamental rights, since it carries out invaluable work in the protection of citizens, often harmed and powerless in the face of decisions of the public Administration.